Innovation in the World of Education Using Information Technology in Learning - Dwi Ana Anggraeni (Konsultan Jurnal Ilmiah Indonesia, 2025)
E-learning is a form of innovation in education that combines information technology with the learning process. The term e-learning refers to the use of technological devices, particularly the internet, to deliver learning materials online. The purpose of this article is to examine educational innovations using information technology in learning. The data collection technique in this study was documentation, collecting and selecting data that correlated with the research title to draw conclusions. The collected data needed to be interpreted by referring to general theory. Data analysis was carried out through the stages of data condensation, data display, and conclusion drawing/verification. E-learning offers significant benefits, such as reduced operational costs, broader access to learning materials, and the use of modern technology to enhance learning effectiveness.